Sex estimation from the talus in a Thai population - Pasuk Mahakkanukrauh (2018)
Previous research on sex estimation from the tarsals has shown that the talus is the most sexually dimorphic tarsal bone in most populations. In order to assess the sexing potential of the talus in a Thai population, 252 skeletons (126 male, 126 female) from the Chiang Mai University Skeletal Collection were measured. The sample represents Thai people who come from the local Chiang Mai area and who died within the past ten years. Ten measurements were taken on the left and right tali from each skeleton. Seven of these measurements are similar, or identical, to measurements used by other researchers. Three experimental measurements were also taken. Logistic regression equations were calculated for each measurement, and for pairs of measurements. The individual measurements were also examined using ROC analysis. Averaging the results from both sides, the individual measurements with the highest correct allocation accuracies based on logistic regression analysis were trochlear length (88.2%), trochlear breadth (87.3%), talar length (85.5%), and inferior articular surface length (84.5%). The ROC results followed a similar pattern, with Area Under the Curve values as follows: trochlear length (0.952), inferior articular surface length (0.937), trochlear breadth (0.935), and talar length (0.914). When pairs of measurements were considered by means of logistic regression, four equations produced predicted allocation accuracies greater than 90% - three from the right talus, and one from the left. The highest accuracy on both sides resulted from a combination of the two most sexually dimorphic individual measurements of trochlear length and trochlear breadth. Together, they produced predicted allocation accuracies of 91.3% on the right side, and 91.4% on the left side. Unlike many past studies that have found talar length to be the most sexually dimorphic measurement of the talus, our study found trochlear length and breadth to be the most accurate measurements for distinguishing the sexes. Researchers developing sexing equations for use with other populations should consider including trochlear length and breadth in their analyses. © 2014 Elsevier Ireland Ltd.